2019
DOI: 10.7759/cureus.5648
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inflammatory Bowel Disease on Pregnancy and the Fetus: A Literature Review

Abstract: Inflammatory bowel disease (IBD) is a constellation of devastating chronic inflammatory changes in the bowel, either involving the large or small bowel or part of both. As it is widely diagnosed in the fertile age group, this disorder can present itself, very commonly, during pregnancy and thus a better understanding of the disease can be an important factor to influence the maternal and fetal well-being. Medications are what is considered the first line in the management of this disease to control the symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…The current study results showed that the activation of the disease might cause preterm birth. Pervez H et al have found IBD to be associated with preterm delivery (18). Morales et al studied the effects of CD on the course of pregnancy, and they reported that exacerbation of the disease was associated with an increased risk of premature labour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study results showed that the activation of the disease might cause preterm birth. Pervez H et al have found IBD to be associated with preterm delivery (18). Morales et al studied the effects of CD on the course of pregnancy, and they reported that exacerbation of the disease was associated with an increased risk of premature labour.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesiolysis was performed in one of those patients (due to rectal bleeding), and surgical resection (due to ileus) was conducted in the other patient. (13,18). Bar-Gil SA et al have found that delivery mode does not influence the natural history of IBD, and vaginal delivery is not associated with an increased risk of subsequent perianal disease in women with CD (10).…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de ella se engloba la enfermedad de Crohn (EC) y la colitis ulcerativa (CU), dos espectros de la enfermedad que pueden tener presentaciones clínicas en común pero difieren en fisiopatología, localización, complicaciones y manejo. La EII puede presentarse en hombres y mujeres, con una mayor incidencia en personas en edad reproductiva, lo que condiciona a una posible presentación de la enfermedad durante el embarazo (1,2). La relación entre el embarazo y la enfermedad inflamatoria intestinal es compleja y aún se encuentra en estudio, ya que se sugiere que los cambios fisiológicos propios del embarazo, principalmente en el sistema inmunológico y la microbiota intestinal, podrían modificar el curso de la EII durante este periodo.…”
Section: La Enfermedad Inflamatoria Intestinal (Eii)unclassified
“…La relación entre el embarazo y la enfermedad inflamatoria intestinal es compleja y aún se encuentra en estudio, ya que se sugiere que los cambios fisiológicos propios del embarazo, principalmente en el sistema inmunológico y la microbiota intestinal, podrían modificar el curso de la EII durante este periodo. Por otro lado, cada vez hay más evidencia que indica que la enfermedad intestinal inflamatoria activa durante la gestación puede aumentar el riesgo de múltiples complicaciones en el embarazo y el parto (1). En esta revisión se hace hincapié en la evidencia que existe hasta el momento sobre la seguridad de los medicamentos más frecuentemente utilizados en la EII y de los fármacos que han surgido más recientemente como opción terapéutica para la enfermedad, como lo es la terapia biológica, específicamente durante el periodo gestacional, con el objetivo de brindar información actualizada de utilidad para los clínicos que se enfrenten al manejo de las EII en pacientes embarazadas que permita un tratamiento efectivo materno y represente, asimismo, el menor riesgo fetal posible.…”
Section: La Enfermedad Inflamatoria Intestinal (Eii)unclassified
“…Colitis is the inflammation of the large intestine resulting in excruciating abdominal pain and discomfort in the body. Sometimes this abdominal pain may be mild or acute and persistent or re-occurring [1,2]. Ulcerative Colitis (UC) is often mistaken for Crohn's Disease (CD) though there are some differences between them.…”
Section: Introductionmentioning
confidence: 99%